UNCONTROLLED DIABETES AS FACTOR AFFECTING COGNITIVE FUNCTION IN TYPE 2 DIABETES MELLITUS - Simanungkalit, Astra Dea; Puspitasari, Vivien; Solansa, Tracy (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Impairment or decline in cognitive function can be caused by various things, one of which is uncontrolled diabetes. In Indonesia, the research on the effect of blood sugar levels on cognitive function has been done, but still limited and less were using HbA1c. Objective: This research aims to find correlation between HbA1C level and cognitive function based on MoCA-Ina. Methods: This is a cross sectional study with a sample of 130 type 2 diabetes mellitus patients at Siloam Hospital Karawaci through a non-randomized purposive sampling method. Data collection was taken on January to May 2020 using medical record data for glycated hemoglobin (HbA1c) levels (cut off score 7%) and Montreal Cognitive Assessment ver. Indonesia (MoCA-Ina) score (cut off score 26) to evaluate the cognitive function. Statistical bivariate analysis performed using chi-square and multivariate analysis covariate variables using logistic regression. Results: Uncontrolled diabetes mellitus as shown by a high HbA1c level were significantly increase the risk of cognitive decline. The study showed a significant relationship between HbA1c levels with cognitive function (OR=5,98; CI 95% 2,25-15,58; p=0,000). A logistic regression analysis of various cognitive functions showed that memory was the most affected domain in patient with uncontrolled type 2 diabetes. Conclusion: Uncontrolled diabetes mellitus as shown by a high HbA1c level were significantly increase the risk of cognitive decline and the most affected domain was memory.